Checklist of mosses (Bryophyta) of Gangetic Plains, India (Bangladesh Journal of Plant Taxonomy, 2016)
An updated account of 79 taxa of mosses of Gangetic plains, representing 40 genera and 19 families, is provided. The family Pottiaceae with 17 taxa belonging to 9 genera appears most dominant and diversified family in the area while at generic level, the genus Fissidens (Fissidentaceae) with 19 species shows maximum diversity, followed by Hyophila and Physcomitrium each with five species.Bangladesh J. Plant Taxon. 23(2): 97-106, 2016 (December)